2022
DOI: 10.1158/1078-0432.ccr-21-3018
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of R-Spondin Fusions and RNF43 Mutations Implicate Novel Therapeutic Options in Colorectal Cancer

Abstract: Purpose: Gene fusions involving R-spondin (RSPOfp) and RNF43 mutations have been shown to drive Wnt-dependent tumor initiation in colorectal cancer (CRC). Herein, we aimed to characterize the molecular features of RSPOfp/RNF43 mutated (mut) compared to wildtype CRCs to gain insights into potential rationales for therapeutic strategies. Experimental Design: A discovery cohort was classified for RSPOfp/RNF43 status using DNA/RNA sequencing and immunohistochemistry. An independent cohort was used to validate our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 46 publications
6
20
0
Order By: Relevance
“…Our analysis revealed that 5.9% of the Middle Eastern CRC patients had RNF43 mutations. This is similar to what has been reported in the largest existing RNF43 study of Seeber et al (6.1%) 32 . Similar frequency of RNF43 mutant cases has also been observed in TCGA cohort where RNF43 mutations were seen in about 5.7% (12/212) of CRC patients 33 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our analysis revealed that 5.9% of the Middle Eastern CRC patients had RNF43 mutations. This is similar to what has been reported in the largest existing RNF43 study of Seeber et al (6.1%) 32 . Similar frequency of RNF43 mutant cases has also been observed in TCGA cohort where RNF43 mutations were seen in about 5.7% (12/212) of CRC patients 33 .…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, RNF43 mutations were found to be significantly enriched in right sided CRCs, which has also previously been reported in other studies 16 , 17 , 32 , 41 , and suggests that RNF43 mutations are associated with distinct primary tumor locations within the colon, further supporting regional differences for Wnt pathway alterations.…”
Section: Discussionsupporting
confidence: 87%
“…Based on recent research reports, the authors identified five previously unreported RSPO fusion events (e.g. IFNGR1 - RSPO3 ) [ 23 ]. Seshagiri et al.…”
Section: Structural Features Of the Rsposmentioning
confidence: 99%
“…RNF43 mutations are frequently truncated frameshift mutations with tandem repeats of microsatellites 46 . Thus, these mutations often occur in sporadic MSI colorectal tumors, with MLH1 mismatch repair gene being the most frequently associated mutation, of right colonic distribution, and CMS1 tumor molecular subtype 47–49 . Fifty percent of sessile serrated lesions are thought to have RNF43 mutations.…”
Section: Regulating Intestinal Epithelial Cell Fatementioning
confidence: 99%
“…46 Thus, these mutations often occur in sporadic MSI colorectal tumors, with MLH1 mismatch repair gene being the most frequently associated mutation, of right colonic distribution, and CMS1 tumor molecular subtype. [47][48][49] Fifty percent of sessile serrated lesions are thought to have RNF43 mutations. Ligand-dependent tumors are rich in mucins, 50 reflected by the fact that RNF43 mutations are seen in 34.5% of genetic mutations responsible for mucinous adenocarcinoma, which are also more commonly associated with MSI.…”
Section: Regulating Intestinal Epithelial Cell Fatementioning
confidence: 99%